Evaluation of the oxidation-nitrosyl stress manifestations at systematic connective tissue diseases - L. A. Alexandrova; N. A. Filippova; T. F. Subbotina; E. S. Alekseevskaya; A. A. Zhloba; V. I. Trofimov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Reduction in antioxidant status with low activity of superoxide dismutase, glutathione peroxidase and glutathione reductase red blood cells at a low level of reduced glutathionein the background and increased NOx levels in blood plasmawas detected in patients with systematic connective tissue and joint diseases: rheumatoid arthritis and ankylosing spondylitis. Detected violations are not correlated with the activity of theprocess, and seropositivity.